Sunlight‐Driven Copper‐Catalyst Activation Applied to Photolatent Click Chemistry. Issue 41 (29th August 2014) - Beniazza, Rédouane; Lambert, Romain; Harmand, Lydie; Molton, Florian; Duboc, Carole; Denisov, Sergey; Jonusauskas, Gedeminas; McClenaghan, Nathan D.; Lastécouères, Dominique; Vincent, Jean‐Marc
Abstract The synthesis, full characterization, photoreduction properties, and catalytic activity for the copper(I)‐catalyzed alkyne‐azide cycloaddition (CuAAC) reaction of a copper(II)–DMEDA (N, N′‐dimethylethylendiamine) complex is reported. Spectroscopic studies (UV/Vis, EPR) demonstrated that under daylight illumination highly effective copper(II) to copper(I) reduction occurs in this complex. These findings are in agreement with a high photoreduction quantum yield value of 0.22 in MeOH, and a value approaching unity as determined in THF. The reduction process, which can also be conducted by irradiation at 365 nm by using a standard TLC (thin layer chromatography) lamp, is ascribed to a highly efficient photoinduced electron transfer (PET) process mediated by the benzophenone photosensitizer present in the carboxylate counterion. Having deaerated the reaction mixture, the photogenerated copper(I) species proved to be highly active for the CuAAC reaction, demonstrated by reactions conducted with low catalyst loading (0.5 mol %) on a range of clickable protected and non‐protected mono‐ and disaccharides. Once initiated, the reaction can be stopped at any time on introducing air into the reaction medium. Deoxygenation followed by irradiation restores the activity, making the copper(II)–DMEDA complex a switchable catalyst of practical value.